2005
DOI: 10.1021/es0504643
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organic Acids in Promoting Colloidal Transport of Mercury from Mine Tailings

Abstract: A number of factors affect the transport of dissolved and particulate mercury (Hg) from inoperative Hg mines, including the presence of organic acids in the rooting zone of vegetated mine waste. We examined the role of the two most common organic acids in soils (oxalic and citric acid) on Hg transport from such waste by pumping a mixed organic acid solution (pH 5.7) at 1 mL/min through Hg mine tailings columns. For the two total organic acid concentrations investigated (20 microM and 1 mM), particle-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 36 publications
(54 reference statements)
0
33
0
Order By: Relevance
“…In the pH range from 1.4 to 6.0, the lower pH, the higher is the loss risk of WDC. Furthermore, with the decreasing pH, total (<1 μm) and colloidal amounts of Al, Fe, Si, and Mn increased, which often acted as the cementitious phase coating or encasing the fines as well as the main composition element of WDCs (Ryan and Gschwend 1994;Swartz and Gschwend 1998;Slowey et al 2005). This suggested that the dissolution of inorganic cement made up by these minerals released some colloidal species, and then portions of Al, Fe, Si, and Mn were transformed from the colloidal species to the dissolved species as well.…”
Section: Inorganic Cement Dissolution At Low Phmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pH range from 1.4 to 6.0, the lower pH, the higher is the loss risk of WDC. Furthermore, with the decreasing pH, total (<1 μm) and colloidal amounts of Al, Fe, Si, and Mn increased, which often acted as the cementitious phase coating or encasing the fines as well as the main composition element of WDCs (Ryan and Gschwend 1994;Swartz and Gschwend 1998;Slowey et al 2005). This suggested that the dissolution of inorganic cement made up by these minerals released some colloidal species, and then portions of Al, Fe, Si, and Mn were transformed from the colloidal species to the dissolved species as well.…”
Section: Inorganic Cement Dissolution At Low Phmentioning
confidence: 99%
“…Soil pH change could significantly influence contaminant transport (Moreira et al 2008), and also the colloid-facilitated P mobility by destroying the inorganic and organic cement of potentially mobilized matrix fines, or cause stronger repulsion by the negatively charged soil matrix and decrease of inter-particle attraction (Klitzke et al 2008). Laboratory experiments have demonstrated that low pH mobilized colloids by inducing the dissolution of inorganic cementing phases, mainly Al and Fe oxides, and clay content (Ryan and Gschwend 1994;Swartz and Gschwend 1998;Slowey et al 2005). In addition, pH is also an important factor affecting the sorption of organic matter on soil and sediment components (Guan et al 2006), which might act as coating around inorganic colloids and hence affect the behavior of colloids.…”
Section: Introductionmentioning
confidence: 99%
“…In nearly all Hg-contaminated natural systems, strong particle association has been identified as the primary mode of transport to aquatic environments, whether from mercury mines (Whyte and Kirchner, 2000;Conaway et al, 2003;Lowry et al, 2004;Kim et al, 2004c;Slowey et al, 2005a), alluvial gold mine tailings (Slowey et al, 2005b), or industry (Gagnon et al, 1997;Rolfhus et al, 2003;Bloom et al, 2004). Although particles account for a minor fraction of Hg deposited from the atmosphere to aquatic settings (Ryaboshapko et al, 2002;Poissant et al, 2004;Sakata and Marumoto, 2005), Hg sorption onto particles enhances downward transport to methylating zones in the water column or sediments (Lamborg et al, 2002).…”
Section: Mercury Speciation and Transportmentioning
confidence: 99%
“…The minerals cinnabar and metacinnabar, native (or elemental) mercury (Hg), calomel (Hg 2 Cl 2 ), and mercury oxychlorides Hg 2 ClO and Hg 4 Cl 2 O have been identified at mercury ore deposits. Mercury sulfide particles are thought to play an important role in the colloid transport of mercury from mercury mine tailings (Lowry et al 2004, Slowey et al 2005. review the absorption behavior of mercury.…”
Section: A145 Mercurymentioning
confidence: 99%